2022
DOI: 10.1144/qjegh2021-087
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of emerging suburban landsliding in Gisborne, New Zealand

Abstract: Recently uplifted, soft Pleistocene sediments in northern New Zealand are particularly vulnerable to landsliding because they are often underlain by less permeable, clay-rich Neogene mudstone/siltstone rocks. Typically, instability is rainfall-induced, often due to a high intensity rainfall event from extra-tropical cyclones, following wetter months when antecedent soil moisture has increased. Using remote sensing, field surveys and laboratory testing, we report on some emerging slope instability hazards in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Identifiable features such as preferential alignment are present and share a similar structure to the smectite-rich soils reported at the Wallis Road landslide in Gisborne (e.g. Cook et al 2022). Indeed, smectite clay minerals are characterised by having very small particles, even among the clay minerals, and well-developed sheet-like structures (Fityus and Buzzi 2009;Meunier 2006).…”
Section: Subsurface Properties and Structurementioning
confidence: 60%
See 2 more Smart Citations
“…Identifiable features such as preferential alignment are present and share a similar structure to the smectite-rich soils reported at the Wallis Road landslide in Gisborne (e.g. Cook et al 2022). Indeed, smectite clay minerals are characterised by having very small particles, even among the clay minerals, and well-developed sheet-like structures (Fityus and Buzzi 2009;Meunier 2006).…”
Section: Subsurface Properties and Structurementioning
confidence: 60%
“…Previous work on soils in Gisborne (e.g. Cook et al 2022) reported smectite was the most common clay mineral, followed by illite on soil-mantled slopes within the Mangatuna Formation and Tolaga Group. Expanding clay minerals would induce The soil at BH2 is a good representation of how soils on the landslide behave once saturated, with high sensitivity (quick clay) and loss of strength upon remoulding, causing high mobility and runout potential.…”
Section: Materials Propertiesmentioning
confidence: 91%
See 1 more Smart Citation
“…The formation comprises alluvial gravels, tephra-rich sands and high plasticity montmorillonite and bentonite (Mazengarb 1997). Previously identified landslides include rotational slumps and earthflows (Cook et al 2022;Davies and Cave 2017), and some failures have been known to occur on slopes with angles as low as 5° (Mazengarb 1997). Shallow soil failures are also common within the regolith overlying the Miocene and Pliocene bedrock in the east of the study area in Wainui, Okitu and Makorori (Fig.…”
Section: Landslide Hazardsmentioning
confidence: 99%
“…Indeed, the extent and ongoing surface deformation of landslides in the Gisborne area are poorly known, and areas at risk from slope instability are often unknown until a slope failure occurs. For example, slope failures have been active at several residential properties in the city (Davies and Cave 2017;Cook et al 2022), where buildings and infrastructure are still at risk from further deformation caused by slow-moving, complex landslides. Also, limited space on the lowlying flood plain means that there is growing incentive to build residential housing on increasingly precarious terrain on slopes surrounding the city.…”
Section: Introductionmentioning
confidence: 99%